Who's Afraid of the 'Artyfyshall Byrd'? Historical Notions and Current Challenges of Musical Artificiality - Cornia, Nicholas 1989-; Forment, Bruno 1978- (2023)
The meteoric surge of AI-generated music has prompted significant concerns among artists and publishers alike. Some fear that the adoption of AI is poised to result in massive job destruction; others sense it will jeopardize and eventually upend all legal frameworks of intellectual property. AI, however, is not the first instance where humanity has confronted the prospect of machines emulating musical creativity. Already in the Baroque, various modes of musical artificiality were explored, ranging from automata and organ stops mimicking human performance and natural sounds, up to devices for mechanized composition (e.g., Athanasius Kircher, Johann Philip Kirnberger, C.P.E. Bach, Antonio Calegari and Diederich Nickolaus Winkel). Valuable insights emerge from the reconsideration—and digital implementation—of these curiosities through the lens of present-day generative models. It can be argued that the very notion of ‘artificiality’ has presented humanity with long-standing philosophical dilemmas, in addressing the debate on the role of art as a substitute of (divine) nature. By digitally implementing and formalizing some pioneering instances of algorithmically generated music we wish to illustrate how mechanical devices have played a role in human art and entertainment prior to our digital era.
FRIS
1
Keywords: Kircher, Athanasius; Kirnberger, Johann Philipp -- 1721-1783; Bach, Carl Philipp Emanuel; Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Artificial intelligence; Automaton; Dance; Algorithmic composition; Game; Baroque